Mechanism of the analgesic effect of electroacupuncture on bone cancer pain through the neuro-immune system: progress based on animal experiments - Qi, Pengfei; Zhou, Mingyuan; Han, Wenqing; Li, Hongxiang; Min, Lu; Li, Jiaxin; Sun, Zhongren; Yin, Hongna (Frontiers in Neurology, 2025)
This article summarizes the mechanism of the analgesic effect of electroacupuncture (EA) on BCP by analyzing the progress of animal experimental research on the treatment of bone cancer pain (BCP). As a kind of chronic specific pain that both overlaps and incompletely coincides with inflammatory pain and neuropathic pain, BCP is mostly clinically treated with opioids such as morphine as the first-line analgesic for BCP, but the long-term application is prone to a series of unavoidable side-effects, such as tolerance, dependence, as well as cognitive impairment, nausea, constipation, and nephrotoxicity. Therefore, there is an urgent need to seek safer and more effective treatment measures. As a safe, reliable and consistently efficacious analgesic, EA produces analgesic effects in inflammatory pain, neuropathic pain and BCP. EA not only attenuates the nociceptive sensitization of BCP by modulating the release of nociception-related neurotransmitters and receptors in the nervous system, but also exerts analgesic effects on BCP by modulating the expression of inflammatory factors in the immune system, inhibiting glial cell activation, and T cell proliferation. At present, EA research on the analgesic mechanism of BCP has made some progress, but there are still problems that need to be solved, such as the lack of standardization of acupoints and parameters, weak clinical validation, a single research model, and limitations in the perspective of analgesic mechanism research. It is suggested that future studies should be based on databases such as AcuEBase v1.0 to develop standardized EA acupoint combinations and frequency parameters to provide a scientific basis for EA standardization. At the same time, the sample size should be expanded and the experimental design should be improved in order to promote the transformation of animal experiments into clinical applications. In addition, it should be expanded to more types of cancer bone metastasis pain models to verify the consistency of the analgesic effect of EA in different BCP models. Future studies could also explore the multi-target synergistic analgesic effects of EA from a microbial-immune axis perspective with the help of tools such as MicrobeTCM. And optimize the treatment plan of BCP through EA combined with drug therapy. It is believed that with the progress of science and technology as well as the continuous exploration of human beings, the complex mechanism of BCP will be overcome by human beings eventually.